Cancers in Australia in 2010 attributable to and prevented by the use of menopausal hormone therapy. (October 2015) - Jordan, Susan J.; Wilson, Louise F.; Nagle, Christina M.; Green, Adele C.; Olsen, Catherine M.; Bain, Christopher J.; Pandeya, Nirmala; Whiteman, David C.; Webb, Penelope M.
Abstract Objectives: To estimate the proportion and number of cancers occurring in Australia in 2010 attributable to menopausal hormone therapy (MHT) use. Methods: We estimated the population attributable fraction for cancers causally associated with MHT (breast, endometrium, ovary), and the proportion of colorectal cancers prevented by MHT. We used standard formulae incorporating Australian prevalence data, relative risks of cancer associated with MHT and cancer incidence. We also estimated potential change in cancer incidence under two hypothetical scenarios whereby 25% fewer Australian women used MHT, or women exclusively used oestrogen‐only MHT. Results: An estimated 539 cancers in Australia in 2010 were attributable to MHT: 453 breast, 67 endometrial and 19 ovarian cancers equating to 3.4%, 3.1% and 1.6% of each cancer type, respectively. In contrast, MHT may have prevented 52 colorectal cancers. If 25% fewer women used MHT, then 141 cancers may have been avoided. If women exclusively used oestrogen‐only MHT then 240 cancers may have been avoided. Conclusions: MHT use caused more than 500 cancers in Australian women in 2010 and prevented ∼50 colorectal cancers. Implications: MHT use continues to cause an excess of cancers. The risks, benefits, regimen and treatment duration should be carefully considered for each woman before MHT is commenced.